AN ANALYSIS OF COHESION OF EXPOSITION TEXTS: AN INDONESIAN CONTEXT - Emilia, Emi; Habibi, Nurfitri; Bangga, Lungguh Ariang (Universitas Pendidikan Indonesia, 2018)
The paper reports on the results of a study aiming to investigate the cohesion of exposition texts written by eleventh graders of a school in Bandung, West Java, Indonesia. The study used a qualitative case study research design, especially text analysis, involving 32 students. In the interest of space, the paper will present the data obtained from six texts written by 6 students, representing low, mid, and high achievers. The texts were analyzed using systemic functional linguistics (SFL), especially in terms of schematic structure and linguistic features, especially those contributing to the cohesion of the texts, such as Theme progression and cohesive devices. The results show that all texts show students? grasp and understanding of the schematic structure of an exposition, including thesis, argument, and restatement of the thesis. All texts also successfully use the zig-zag and the Theme reiteration patterns, which indicate the students? emerging capacity to create a text with cohesion at the clause level. However, only texts written by high achievers employ the multiple Theme pattern, indicating the students? emerging capacity to create a text with better sense of connectedness, unity, and flow of information at the global level. High achiever texts also employ discourse features which allow the reader to predict how the text will unfold and guide them to a line of understanding of a text as a whole. Moreover, in terms of cohesive devices, all texts use some simple cohesive devices?reference, lexical cohesion, and conjunction. It should be mentioned that all texts are rudimentary with some inappropriate word choices and grammatical problems. This suggests that the students still needed more guidance and time to do research on the topic in focus, to go through the process of writing as professional do, to allow them to create a better text with more elaboration and characteristics of written language with consistency and accuracy. It is recommended that further research on different perspectives and foci of analysis of different text types using systemic functional linguistics, with more representative samples, and studies on the teaching of writing be conducted.